2015
DOI: 10.1136/bmjopen-2014-006131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of once-daily indacaterol maleate/mometasone furoate on exacerbation risk in adolescent and adult asthma: a double-blind randomised controlled trial

Abstract: ObjectiveTo investigate the safety and efficacy of QMF149, a once-daily, fixed-dose combination of the long-acting β2-agonist (LABA) indacaterol maleate and inhaled corticosteroid (ICS) mometasone furoate (MF) for the treatment of persistent asthma. The hypothesis was that QMF149 would not increase the risk of serious asthma exacerbations.Setting174 research centres in nine countries.Participants1519 adolescents and adults with persistent asthma who were treated or qualified for treatment with combination LABA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
4
14
0
1
Order By: Relevance
“…All reported AEs were mild in intensity, and no serious AE was reported. These safety findings are in agreement with those of a previous study conducted in patients with asthma …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…All reported AEs were mild in intensity, and no serious AE was reported. These safety findings are in agreement with those of a previous study conducted in patients with asthma …”
Section: Discussionsupporting
confidence: 93%
“…These safety findings are in agreement with those of a previous study conducted in patients with asthma. 12 This study assessed the contribution of lung and GI absorption to the total systemic exposure of indacaterol and mometasone furoate following oral inhalation of QMF149 via the TH device. The data from this study indicate that lung and GI absorption accounted for 25% and 75%, respectively, of the total systemic exposure of indacaterol.…”
Section: Discussionmentioning
confidence: 99%
“…Formoterol has a rapid onset of bronchodilation, and is approved for the acute relief of airflow obstruction in many countries, unlike salmeterol, whose onset to peak bronchodilation takes significantly longer than formoterol 16 . More recently, the benefit of ultra-long acting LABAs, such as vilanterol, have been demonstrated when added to an ICS in asthma 11,17 , and this combination has been approved for use in many countries, while others are still under clinical development for use in asthma 12,18 .…”
Section: Efficacy Of Inhaled β 2 -Agonistsmentioning
confidence: 99%
“…Indacaterol is an uLABA registered for use in treatment of patients with COPD in the USA and Europe. The results of a randomised, double-blind clinical trial demonstrated that indacaterol in combination with mometasone furoate was at least as efficacious as mometasone with respect to the time to the first serious asthma exacerbation (0.3% vs. 0.8%; p = 0.16) [28]. A combination of indacaterol and mometasone was superior to mometasone www.pneumonologia.viamedica.pl alone with respect to the total number of asthma exacerbations requiring oral glucocorticosteroids per year (rate ratio: 0.71; 95% CI: 0.55 to 0.90; p = 0.005).…”
Section: New Treatment Optionsmentioning
confidence: 99%